Bhāminīvilāsa of Jagannātha : with Kāvyamarmaprakāśa of Lakshman Ramchandra Vaidya : Sanskrit text, study, introduction, English translation, prose order, notes and appendices - Jagannātha Paṇḍitarāja (Bharatiya Kala Prakashan, 2004)
Classical poem with Kāvyamarmaprakāśa Sanskrit commentary and English translation; includes study of the text.